A ten-year evaluation of central nervous system cystic echinococcosis in a highly endemic area of Iran: Molecular epidemiology and clinicopathological characteristics - Mohsen Najjari; Ali Dehesht Manesh; Shahab Rezaeian; Bibi Razieh Hosseini Farrash; Mohammad Ali Mohammadi; Mohammad Ebrahimipour (Parasite Epidemiology and Control)
Cystic echinococcosis can involve various organs in humans with the brain and spine being particularly vulnerable. This research aimed to study clinicopathological features and molecular analysis of the central nervous system (CNS) echinococcosis cases in a central hospital for hydatid cyst surgery in northeastern Iran. CNS echinococcosis cases from surgically managed human CE cases at Ghaem hospital in northeastern Iran were analyzed from 2012 to 2022. Demographic and clinicopathological data were collected for CNS echinococcosis cases and formalin-fixed paraffin-embedded (FFPE) blocks were used for molecular analysis. The total prevalence of CNS echinococcosis cases was 1. 8 %. Most of the CE cases were reported in women (64. 7 %) and from rural areas (58. 8 %). The highest number of cases (41. 2 %) were aged ≤18 years, with majority being ranchers (47. 1 %). Thirteen cases (76.5 %) were found to have cysts in their brain, particularly in the supratentorial site. Headache was the most commonly reported sign in cases (9/13, 69.2 %). Infiltration of eosinophils, polymorphic inflammatory cells, and giant cells, gliosis, and foreign body granulomatous reaction, along with mild infiltration of mononuclear cells showing degeneration and necrotic foci in the brain infections. Spine infections included bone cartilage, ligaments, and hydatid cyst wall fragments. PCR analysis conducted on 17 samples revealed the presence of 13 isolates of E. granulosus sensu lato. Among these, 11 were classified within the E. granulosus sensu stricto (G1 and/or G3) complex, while 2 isolates were identified as belonging to the E. canadensis G6/G7. Cerebrospinal infection is a significant aspect of CE cases in northcentral Iran, with a higher prevalence among women and in rural areas. Children were the most affected age group, with the E. granulosus s.s. genotypes being the most common.